N `-[(2-n-Butyl-4-chloro-1H-imidazol-5-yl)methylidene]adamantane-1-carbo hydrazide sesquihydrate ethanol hemisolvate - Al-Tamimi, Abdul-Malek.S.; Bari, A.; Al-Omar, M.A.; El-Emam, A.A.; Ng, S.W. (International Union of Crystallography, 2010)
In the asymmetric unit of the title compound, C(19)H(27)ClN(4)O center dot 0.5C(2)H(6)O center dot 1.5H(2)O, there are two molecules of the Schiff base, which has a rigid adamantyl cage at one end of the C(= O)NH-N=CH- chain and an almost planar [torsion angles = 1.3 (1) and 7.9 (2)degrees imidazolyl ring at the other end, three molecules of water and one molecule of ethanol. In both independent molecules of the Schiff base, this chain displays an extended zigzag configuration. All their amino groups function as hydrogen-bond donors to water molecules; these are linked to other acceptor atoms, generating a layer structure. O-H...O and O-H...N interactions involving the water molecules also occur.